2019
DOI: 10.20869/auditf/2019/153/002
|View full text |Cite
|
Sign up to set email alerts
|

Audit Quality and Several of Its Determinants

Abstract: The objective of this article is to identify the relationship between the quality of services provided by the financial auditors and its determinants, among which the initial and continuing training of auditors occupies an important place as long as their authorization depends on achieving an adequate level of education and professional training. It has been taken into account the fact that the purpose of public interest entities has become global, and the ethical and professional challenges to which auditors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It is also important that auditors should keep pace with the rapid developments in both their job and IT in order to meet society's needs. The employment of IT in the audit field helps build an electronic base for customers and select the audit sample more accurately (Chersan, 2019). Moreover, auditors' performance related to computerized AIS risks affecting the quality of their work and how to deal with such risks should be improved by means of conducting training courses.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important that auditors should keep pace with the rapid developments in both their job and IT in order to meet society's needs. The employment of IT in the audit field helps build an electronic base for customers and select the audit sample more accurately (Chersan, 2019). Moreover, auditors' performance related to computerized AIS risks affecting the quality of their work and how to deal with such risks should be improved by means of conducting training courses.…”
Section: Resultsmentioning
confidence: 99%
“…To theoretically clarify the underlying relationships between the independent and the dependent variables; the current study builds upon the results of previous studies. In this regards, some previous studies (e.g., Halabi & Chowdhury, 2018;Murphy, 2017;Paisey et al, 2007;Paisey & Paisey, 2018;Paisey and Paisey, 2014) indicated that the CPD of accounting, business and financial knowledge have a positive contribution to the quality of the internal audit; likewise, other studies (e.g., Paisey & Paisey, 2018;Tudora, 2013;Mattli & Buthe, 2005;Chersan, 2019;Lee, 1995;Baker, 2005) have indicated that the CPD of the technical competence of the financial auditing has an actual contribution to the quality of the internal audit. Furthermore, a group of studies (Seol et al, 2011;Plant et al, 2019;Kaspina, 2015;Firth et al, 2012;Lenz and Hanh, 2015;Krá l et al, 2017;Siriwardane et al, 2014;Ahmad et al, 2019) showed that the CPD of the professional skills of the internal auditors has a positive contribution to the quality of the internal audit.…”
Section: The Study Modelmentioning
confidence: 90%
“…IAESB (2015, IES 8, 7) states: 'The aim of this IES 8 is to ensure that professional accountants acquire and maintain the specific capabilities required to work as competent audit professionals.' Such studies have primarily centred on public interest, as well as audit quality in the context of it being a significant goal of CPD (e.g., Paisey & Paisey, 2018;Tudora, 2013;Mattli & Buthe, 2005;Chersan, 2019;Lee, 1995;Baker, 2005). The body (IAESB) meanwhile indicates:…”
Section: "Scope Of This Standard (Ies7) Prescribes the Continuing Promentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the factors, the auditor's correct reasoning and ethical actions can lead to a qualitative audit. For this, however, an auditor must have a high level of professional knowledge and skills and have assimilated the ethical behaviour imposed by professional and societal norms (Chersan, 2019). The consolidation of the company's image, as well as the increase of the reputation among customers and stakeholders, is done by adopting a socially responsible behaviour, a behaviour superior to ethical reasons, to which the solution of social and environmental problems can effectively contribute (Socoliuc et al, 2020).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%